The rate of NSAID‐induced endoscopic ulcers increases linearly but not exponentially with age: a pooled analysis of 12 randomised trials - Boers, Maarten (BMJ Group, 2007)
The risk of major ulcer complications on treatment with non‐steroidal anti‐inflammatory drugs (NSAIDs) is known to increase exponentially with age. However, in a pooled analysis of 12 trial arms, the incidence of endoscopic ulcers on treatment with NSAID was found to increase with age in a roughly linear fashion. Thus, it is concluded that increasing age is associated with both more frequent and more serious NSAID gastropathy.